The Use of CSR Measurement Matrix in the Aspect of Sustainable Development - Anna Klepacka; Monika Bagińska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The idea of Corporate Social Responsibility (CSR) represents the voluntary effort that companies invest in social life. Companies incorporate the concept of CSR strategy in their businesses, knowing its importance to the benefit of the public at large and to sustainable development. Any activity of any major company is exposed to public opinion, which plays a key role in shaping the image of the company. Companies compete to win social trust and acceptance of their activity. The aim of the article was to present the value and significance of CSR activities undertaken by companies, using the example of two businesses, i.e. Polski Koncern Naftowy (PKN) Orlen and Kompania Piwowarska in reference to sustainable development. The article compares the CSR measurement matrix that allows assessing whether a given company is socially responsible, to what extent CSR activities affect the company's stakeholders and to what extent they are consistent with sustainable development (assigning particular CSR development tools by Stakeholders applying the weights from 1 to 3). ISO 26000 standards define the principles of social and environmental responsibility as a guide for organizations and in the analysed companies are a tool that exerts one of the greatest impacts on stakeholders. For both companies, the most important stakeholders are Shareholders and Managers, and they are the ones who, to the largest extent, conduct a socially responsible dialogue for which all CSR development tools are important. Both companies conduct key activities, PKN Orlen used 91% and Kompania Piwowarska 73% of all CSR development tools considered in this study.